2020
DOI: 10.3389/fpsyg.2020.00372
|View full text |Cite
|
Sign up to set email alerts
|

Community Characteristics, Victimization, and Psychological Adjustment Among School-Aged Adopted Children With Lesbian, Gay, and Heterosexual Parents

Abstract: Little research has examined victimization among school-aged children raised in lesbian/gay (LG) parent households and almost no work has attended to the school and community contexts that may impact their victimization risk. This study examined predictors of parent-reported child victimization and child adjustment, and parent responses to victimization, in 43 two-mother, 37 two-father, and 56 mother-father families, with adopted children (median age = 8.6 years). Predictors included parent (sexual orientation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 72 publications
2
21
0
Order By: Relevance
“…Importantly, when considered at the between-group level, children’s adjustment in LGBTQ+ parent families is similar to those raised in heterosexual, cisgender families [ 69 , 70 ], indicating that possible peer victimization experiences due to the family structure (or other minority stressors) are not driving adjustment disparities. However, within children in LGBTQ+ parent families, victimization and stigmatization have been found to be associated with higher levels of internalizing and externalizing problems [ 3 , 8 , 71 , 72 , 73 , 74 , 75 ], but not with substance use [ 76 ].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, when considered at the between-group level, children’s adjustment in LGBTQ+ parent families is similar to those raised in heterosexual, cisgender families [ 69 , 70 ], indicating that possible peer victimization experiences due to the family structure (or other minority stressors) are not driving adjustment disparities. However, within children in LGBTQ+ parent families, victimization and stigmatization have been found to be associated with higher levels of internalizing and externalizing problems [ 3 , 8 , 71 , 72 , 73 , 74 , 75 ], but not with substance use [ 76 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this vein, the results add novel insights to the literature on the effect of stigmatization in new and emerging family forms (Bos & Gartrell, 2010;Bos & van Balen, 2008;Carone et al, 2018;Farr et al, 2016;Farr & Vázquez, 2020;Goldberg & Garcia, 2020;Golombok et al, 2018;Green et al, 2019;van Gelderen et al, 2009, van Rijn-van Gelderen et al, 2015. Although explicit and overt forms of discrimination and microaggressions differ in form and content, the present findings demonstrate that subtle and implicit prejudice is equally detrimental to the father-child relationship.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 73%
“…It has been suggested that, because most people in contemporary times do not engage in overtly hostile or consciously biased behavior toward members of targeted social groups, discrimination against new family forms does not exist in a major way (Massey, Merriwether, & Garcia, 2013). However, research with families headed by sexual minority parents (e.g., gay fathers through surrogacy, adopted children with gay and lesbian parents, donor-conceived children, and adolescents with lesbian mothers) has demonstrated that people tend to uphold both explicit biases (i.e., prejudice that is conscious and known) and implicit biases (i.e., prejudice that is unconscious and unknown) against these families (Bos & Gartrell, 2010; Bos & van Balen, 2008; Carone, Lingiardi, Chirumbolo, & Baiocco, 2018; Farr, Crain, Oakley, Cashen, & Garber, 2016; Farr & Vázquez, 2020; Goldberg & Garcia, 2020; Golombok et al, 2018; Green, Rubio, Rothblum, Bergman, & Katuzny, 2019; Haines, Boyer, Giovanazzi, & Galupo, 2018; van Gelderen, Gartrell, Bos, & Hermanns, 2009; van Rijn-van Gelderen, Bos, & Gartrell, 2015). This being the case, it is likely that gay and heterosexual single fathers through surrogacy (and their children) suffer from some degree of stigma and discrimination as a result of their family form.…”
Section: Microaggressions Against Single Fathers Through Surrogacymentioning
confidence: 99%
“…Risk of bias was mainly related to confounding factors, or non-objective measures of exposure factors (online supplemental appendix S2). The included 34 studies were categorised into the following three areas including 11 main themes: children’s developmental outcomes (17 for children’s psychological adjustment,18 20 25–39 five for children’s physical health,19 20 37 38 40 four for children’s gender role behaviour,26 35 41 42 three for children’s gender identity/sexual orientation,20 29 41 six for children’s educational outcomes,20 33 43–46 parents’ psychological adjustment (six for parental mental health,18 27 35 36 47 48 five for parenting stress,32 35 40 48 49 household-level outcomes (six for parent–child relationship,30 35 36 40 47 50 six for couple relationship satisfaction,26 28 31 40 48 51 four for family functioning,25 26 28 49 three for social support,32 52 53 and five outcomes that cannot be grouped into themes (preschool selection considerations,54 parental school involvement,55 parent-school relationships,27 parental self-agency,28 and child’s substance use 30. The outcome measures in table 1 were listed in the order of the above themes.…”
Section: Resultsmentioning
confidence: 99%